Numerical Solutions of Some Partial Differential Equations Using Galerkin-Finite Element Method - Chopra, Aanchal (My University, 2012)
In this thesis an attempt has been made to solve some parabolic partial differential equations by using finite differences methods.
Keywords: Finite Element Method, Burger's Equation, Advection-diffusion Parabolic Partial Differential Equation